GREENHOUSE GAS EMISSIONS DISCLOSURE ON FIRM VALUE AND FINANCIAL PERFORMANCE IN EU-ETS MEMBER COUNTRIES - Pramesti, Retta Farah; Sueb, Memed (Jurnal Akuntansi dan Keuangan Indonesia, 2026)
Background: Climate change and regulatory frameworks such as the European Union Emission Trading System (EU ETS) have increased pressure on firms to manage and disclose greenhouse gas (GHG) emissions. However, the financial and market consequences of GHG emissions and disclosure remain debated. Method: This study employs a quantitative causal-comparative design using secondary data from the Refinitiv database for 2015–2024. The sample consists of 2,315 European firms participating in the EU ETS. Regression analysis is conducted to examine the effects of GHG emissions and their disclosure on firm value, return on assets (ROA), and return on equity (ROE), with firm size and capital structure as control variables. Signaling theory underpins the analysis. Findings: GHG emissions and their disclosure significantly affect firm value and show a weak but positive effect on ROA, while they do not significantly influence ROE. The findings indicate that sustainability-related factors are more strongly reflected in market valuation and short-term asset efficiency than in equity-based profitability. Conclusion: Effective GHG management and transparent disclosure enhance market value and operational performance but do not directly improve shareholder returns. Novelty/Originality of this article: This study provides recent evidence from EU ETS firms, focusing specifically on GHG emissions and disclosure within a regulated European context.